Passive acoustic monitoring reveals feeding attempts at close range from soaking demersal longlines by two killer whale ecotypes. Issue 1 (3rd September 2021) - Richard, Gaëtan; Bonnel, Julien; Beesau, Julie; Calvo, Eva; Cassiano, Fabio; Dramet, Maéva; Glaziou, Aziliz; Korycka, Kinga; Guinet, Christophe; Samaran, Flore
Abstract: Odontocetes depredating fish caught on longlines is a serious socio‐economic and conservation issue. A good understanding of the underwater depredation behavior by odontocetes is therefore required. Historically, depredation on demersal longlines has always been assumed to occur during the hauling phase. In this study, we have focused on the depredation behavior of two ecotypes of killer whales, Orcinus orca, (Crozet and Type D) from demersal longlines around the Crozet Archipelago (Southern Indian Ocean) using passive acoustic monitoring. We assessed 74 hr of killer whale acoustic presence out of 1, 233 hr of recordings. Data were obtained from 29 hydrophone deployments from five fishing vessels between February and March 2018. We monitored killer whale buzzing activity (i.e., echolocation signals) as a proxy for feeding attempts around soaking longlines. These recordings revealed that the two ecotypes were feeding at close range from soaking longlines, even when fishing vessels were not present. Our results suggest that both killer whale ecotypes are likely to depredate soaking longlines, which would imply an underestimation of their depredation rates. The implication of underestimating depredation rates is inaccurate accounting for fish mortality in fisheries' stock assessments.